2015
DOI: 10.1155/2015/752936
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility in relation to Landscape Position and Land Use/Cover Types: A Case Study of the Lake Kivu Pilot Learning Site

Abstract: This study determined the change and distribution of land-uses/covers along the landscape, and evaluated the nutrient status of the top soil layer in the Lake Kivu Pilot Learning Site (LKPLS) benchmarked micro-catchments. Soil physical and chemical properties were quantified using triplicate soil samples collected from each land-use/cover at two depths (0-15 and 15-30 cm) in three LK PLS Learning Innovation Platform (IP) sites (Bufundi in Uganda, Mupfuni-Shanga in D.R. Congo, Gataraga in Rwanda). Small scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…If adding N relieves the bacterial growth limitation, it is possible that the competitive potential of the bacterial community increases relative to that of fungal community, resulting in a decrease in fungal growth. Mille-Lindblom and Tranvik (2003) found an interaction between fungal and bacterial growth on submerged plant material. The results revealed that the presence of bacteria inhibited the fungal growth.…”
Section: Notementioning
confidence: 97%
See 1 more Smart Citation
“…If adding N relieves the bacterial growth limitation, it is possible that the competitive potential of the bacterial community increases relative to that of fungal community, resulting in a decrease in fungal growth. Mille-Lindblom and Tranvik (2003) found an interaction between fungal and bacterial growth on submerged plant material. The results revealed that the presence of bacteria inhibited the fungal growth.…”
Section: Notementioning
confidence: 97%
“…The N availability is an important determinant of the soil microbial community (Leff et al, ). Landscape positions are also a key factor that can impact soil properties (Mwanjalolo Jackson‐Gilbert et al, ). Footslope positions are generally rich in moisture, organic matter, clay content and thus tend to have higher primary productivity in comparison with upland areas.…”
Section: Introductionmentioning
confidence: 99%
“…CHELSA; [ 29 ]), edaphic variables vary at local scales and with great complexity [ 30 ]. For example, within the same landscape, climatic conditions can be very homogenous throughout while soil properties can vary widely according to different parental material [ 31 ], topographic position [ 32 ] or land-use [ 33 ]. Indeed, there are several examples in the literature where soil properties control the distribution of plant species or the structure, composition, and physiognomy of a community within an otherwise climatically homogeneous geographical extent.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape position also may play a key role in the C sequestration potential of switchgrass. Soil properties can vary dramatically by hillslope (Jackson‐Gilbert et al, 2015), with significant impacts on root growth. Earlier studies by Bronson et al (2003) and Guzman and Al‐Kaisi (2011) emphasized the major influence that topographic positions in different landscapes have on soil properties.…”
mentioning
confidence: 99%